Supply and distribtion of fertilizers in Bangladesh - Quasem, Abul Md. (International Food Policy Research Institute, 1987)
The availability of fertilizers "at the right time, in the right quantity, and at the right places" is considered crucial to expanding agricultural production through increasing fertilizer use. Even if farmers are aware of the benefits of fertilizer application, they would not be able to use fertilizers without adequate availability at their usual marketplaces when application to particular crops is most propitious. The critical nature of timely availability is compounded by the inability of farmers, for a variety of reasons, to store chemical fertilizers for more than a few days.